(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The growth of a society totally depends on its social and economic development. This is the basic reason why socio-economic surveys are carried out. This type of survey includes both spatial and non-spatial datasets. LULC maps play a significant and prime role in planning, management and monitoring programmes at local, regional and national levels. Therefore, this study sought to integrate the remotely sensed data and geographical information system (GIS) techniques to map and classify the area of district Bilaspur in Himachal Pradesh India . Multi-temporal satellite images of 1989, 1999, 2009 and 2019 were pre-processed, geo-referenced, and mapped using the supervised maximum likelihood classification to examine land use and land cover .This type of information, on one hand, provides a better understanding of land utilization aspects and on the other hand, it plays an important role in the formation of policies and programme required for development planning. For ensuring sustainable development, it is necessary to monitor the on-going process on land use/land cover pattern over a period of time. .